TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Talitha Ammara Widodo; Sadiyyah (STKIP Subang, 2026)
Aggravated theft is one form of property crime that occupies a relatively high position in Indonesia's crime rate. Unlike ordinary theft as regulated under Article 362 of the Indonesian Criminal Code (KUHP), aggravated theft is accompanied by particular circumstances that increase the offender's degree of culpability, such as being committed at night, by two or more persons acting in concert, or by breaking in or climbing into a building. This study aims to examine the meaning, elements, criminal sanctions, and criminal liability of offenders of aggravated theft under Article 363 of the KUHP. The study employs a normative juridical method using a statute approach and a conceptual approach, with data obtained through literature study of primary, secondary, and tertiary legal materials, analyzed descriptively and qualitatively. The results show that an act can only be qualified as aggravated theft when all general elements of theft under Article 362 are fulfilled together with at least one aggravating element under Article 363. The maximum penalty is seven years' imprisonment, which may increase to nine years where more than one aggravating circumstance concurs. The offender's criminal liability depends on capacity for responsibility and the absence of justification or excuse grounds, and may be extended through the concept of participation (deelneming) under Articles 55 and 56 of the KUHP. The enactment of Law Number 1 of 2023 on the Criminal Code in 2026 brings adjustments that warrant close attention from both law enforcement officials and legal scholars.